Dampak Pelatihan Menggunakan High Intensity Interval Training Terhadap Peningkatan Hasil Ergometer Rowing Test 6000 M - Widayani Widayani; Dede Rohmat Nurjaya; Dadan Mulyana; Mulyana Mulyana (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2022)
Rowing is the dominant endurance sport, so rowing trainers must be more observant in providing forms of training to improve physical condition, especially in the endurance component. The High Intensity Interval Training (HIIT) method was chosen as the training method used to improve the results of the 6000 m rowing test ergonometer. The purpose of this study was to determine the effect of the High Intensity Interval Training (HIIT) method on the results of increasing the 6000 m rowing test ergometer. The method used in this study is an experimental method with a research design of One Group Pre-test Post-test Design. 4 Rowing athletes in Bandung were selected and used as samples in this study. The training was carried out for 4 weeks with a total of 12 meetings and 3 meetings a week. The instrument used is a rowing ergometer 6000 m test. The results of this study showed that there was an effect of the high intensity interval training (HIIT) method on the 6000 m rowing test ergometer.